Study on the Underlying Mechanism of Yinhua Gout Granules in the Treatment of Gouty Arthritis by Integrating Transcriptomics and Network Pharmacology - Fan QQ; Zhai BT; Zhang D; Zhang XF; Cheng JX; Guo DY; Tian H (Dove Medical Press, 2024)
Qiang-qiang Fan,1 Bing-tao Zhai,1 Dan Zhang,1 Xiao-fei Zhang,1 Jiang-xue Cheng,1 Dong-yan Guo,1- 3 Huan Tian4 1School of Pharmacy, Shaanxi University of Chinese Medicine, Xi'an, 712046, People's Republic of China; 2Shaanxi Key Laboratory of Chinese Medicine Fundamentals and New Drugs Research, Shaanxi University of Chinese Medicine, Xi'an, 712046, People's Republic of China; 3State Key Laboratory of Research & Development of Characteristic Qin Medicine Resources (Cultivation), Shaanxi University of Chinese Medicine, Xi'an, 712046, People's Republic of China; 4Xi'an Hospital of Traditional Chinese Medicine, Xi'an, 712046, People's Republic of ChinaCorrespondence: Dong-yan Guo; Huan Tian, Email 2051080@sntcm.edu.cn; 18149412681@163.comPurpose: Yinhua Gout Granules (YGG) is a traditional Chinese medicine preparation with a variety of pharmacological effects, and its clinical efficacy in the treatment of gouty arthritis (GA) has been fully confirmed. However, the pharmacodynamic basis of YGG and its anti-inflammatory mechanism of action in GA are unknown. The objective of this study was to identify the active components and molecular mechanisms of YGG in the treatment of GA.Methods: Ultra-performance liquid chromatography-electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) and network pharmacology were used to identify and predict the potential active ingredients and related signaling pathways. Then, we revealed the anti-GA effects of YGG based on pharmacodynamic experiments in GA rats. Finally, we integrated transcriptomics and network pharmacology to elucidate the potential mechanism of action and verified the putative mechanism by molecular docking, immunohistochemical (IHC) and Western blot.Results: We have identified 10 major active components of YGG that may have anti-GA effects, such as ferulic acid, rutin, luteolin, etc. Using molecular docking, we found that 10 major compounds could bind well to TNF, PTGS2, IL-6, IL1β, NOS2 and PTGS1, and the binding energies were all less than − 5 kcal/mol. Animal studies have shown that YGG can improve joint inflammation and inflammatory cell infiltration, reduce serum UA, BUN and Cr levels (p